Implementation of Financial Literacy in Increasing Financial Awareness and Security - Nabila Izmi Aina; Fauzi Arif Lubis; Fitri Hayati (Proceeding International Conference on Islamic Economics Community Services (ICIECS), 2023)
This article examines the effectiveness of implementing financial literacy programs in enhancing financial awareness and security. The study uses a focus group and discussion approach to investigate how these programs influence individuals' understanding and management of personal finances. By engaging with financial literacy experts, educators, and community participants, the research delves into how financial literacy impacts behavior, decision-making, and overall financial well-being. The results reveal that financial literacy programs significantly improve individuals' ability to manage their finances, make informed financial decisions, and understand key financial concepts such as budgeting, debt management, and investment. Participants report increased confidence in handling their personal finances and a better grasp of financial risks and opportunities. The study also highlights that effective financial literacy fosters positive attitudes towards financial planning and enhances financial resilience. Overall, financial literacy plays a crucial role in shaping a more financially aware and secure society. The article concludes with policy recommendations to further improve the effectiveness of financial literacy programs, emphasizing the need for tailored educational strategies and collaborative efforts between educational institutions, financial organizations, and community groups.